Successful Management of Quadriceps Contracture in a Cat - Mohammad Akbari; Zahra Shamsi; Mehdi Behfar (Iranian Journal of Veterinary Surgery, 2024)
A six-month-old female domestic short hair cat was presented for bilateral hindlimb lameness. Radiographt revealed bilateral distal femoral physeal fractures and left sided acetabular fracture. Treatment performed by transfixation cross pinning for both limbs. The right hind limb was operated immediately, however, due to an open fracture on the left hind limb, the surgical intervention was postponed to prevent osteomyelitis. The delayed surgical intervention was associated with quadriceps contraction. Here, to treat the muscle contraction, muscle release operation followed by a 90 degree external coaptation was performed. After healing of the surgical wound, physiotherapy with neuromuscular electrical stimulation was performed for five sessions over three weeks and then the cat demonstrated significant improvement in the posture and gait. Quadriceps contraction often is observed as a complication during healing of femoral fracture after surgery. Physiotherapy may play important role in preventing postoperative pain and other complications.